Production of tumor necrosis factor-a is increased in urinary tract infections - Neni Susilaningsih; Bambang Joni Karjono; Ratna Damma Purnamawati (Universa Medicina, 2012)
BACKGROUND Urinary tract infection (UTI) is a common source of bacteriemia. The most common cause of UTI is Escherichia coli (E. coli). Tumor Necrosis Factor (TNF)-á gene polymorphism has been reported to be responsible for an excessive production of TNF-á and eventual disruption of pro-inflammatory cytokine regulation. The aim of this study was to compare TNF-á serum levels and TNF-á allele polymorphisms in patients with UTI due to E.coli and in non- UTI controls. METHODS A cross-sectional study was conducted at Dr. Kariadi Central Hospital and the Center for Biomedical Research, Faculty of Medicine, Diponegoro University, Semarang. In 68 patients with UTI the TNF-á serum levels were determined by means of ELISA and compared to those of non-UTI controls (n=55). TNFá- 308G>A gene polymorphism was analyzed by polymerase chain reaction restriction fragment length using the NcoI enzyme. Fragments were visualized on polyacrylamide gel with silver staining. RESULTS TNF-á serum level in patients with UTI had a median of 8.9 pg/mL, which was significantly higher than the median of 3.7 pg/mL in the control group (pA gene polymorphisms found in the patient group were G/G=61 (90%), G/A=7(10%) and A/A=0, while in the control group were G/G=48 (87%), G/A=7 (13%) and A/A =0. There was no significant differences (p=0.578) in gene polymorphisms between the two groups. CONCLUSIONS TNF-á serum levels in patients with UTI due to E. coli were significantly higher than in non-UTI controls, but for the TNF-á-380 gene polymorphisms no significant difference was found between the two groups. There are presumably more important factors than host genotype that influence UTI pathogenesis.